2022
DOI: 10.1039/d2ob01418a
|View full text |Cite
|
Sign up to set email alerts
|

On the potential intermediacy of PhIBr2 as a brominating agent

Abstract: PhIBr2, first purported to exist over 100 years ago, has been subject of few reports due to its low stability. However, a recent publication proposes a reaction of PIFA (PhI(OC(O)-CF3)2)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…While we were undertaking this study Periana and co-workers isolated and spectroscopically characterized C 6 F 5 –I(NTf 2 ) 2 and showed that at elevated temperatures and pressures direct C–H activation of simple alkanes is possible. 13 They did not however confirm the structure by X-ray crystallography and in light of the previous misidentifications of PhI(OTf) 2 , as well as other recent cases involving structural misassignment of I( iii ) complexes, 14–16 it is important that structural confirmation of ArI(NTf 2 ) 2 is obtained. In this report we structurally characterize NO 2 –C 6 H 4 –I(NTf 2 ) 2 and provide analysis that shows these NTf 2 ligated species are significantly stronger oxidizing agents than NO 2 –C 6 H 4 –I(OTf) 2 , representing the current frontier in the oxidative ability of ArIL 2 and possibly the limit for this class of compound.…”
mentioning
confidence: 90%
“…While we were undertaking this study Periana and co-workers isolated and spectroscopically characterized C 6 F 5 –I(NTf 2 ) 2 and showed that at elevated temperatures and pressures direct C–H activation of simple alkanes is possible. 13 They did not however confirm the structure by X-ray crystallography and in light of the previous misidentifications of PhI(OTf) 2 , as well as other recent cases involving structural misassignment of I( iii ) complexes, 14–16 it is important that structural confirmation of ArI(NTf 2 ) 2 is obtained. In this report we structurally characterize NO 2 –C 6 H 4 –I(NTf 2 ) 2 and provide analysis that shows these NTf 2 ligated species are significantly stronger oxidizing agents than NO 2 –C 6 H 4 –I(OTf) 2 , representing the current frontier in the oxidative ability of ArIL 2 and possibly the limit for this class of compound.…”
mentioning
confidence: 90%
“…However, the literature does not present reports of utilizing 9 as reagents or catalysts in enantioselective bromo functionalizations. 23 However, recent studies by Wilson and Dutton showed that PhIBr 2 is an elusive compound, 24 making the application of linear bromo iodanes not feasible here. Therefore, we wondered if we could use the corresponding, more stable chloro iodanes instead to synthesize 4 in optically pure form.…”
Section: Table 1 Hypervalent Iodine Mediated Chlorinati...mentioning
confidence: 99%
“…When anisole is reacted with molecular bromine, the reaction only takes 10 minutes at room temperature, demonstrating how unreactive this I–Br compound is in comparison to Br 2 itself. 7…”
Section: Introductionmentioning
confidence: 99%
“…8 However, we found that conditions that claimed to give PhIBr 2 are in fact generating in situ molecular bromine, which acts as the brominating agent. 7…”
Section: Introductionmentioning
confidence: 99%